An interdisciplinary study of the plumbing system and eruption dynamics at Marapi volcano (Sumatra, Indonesia) - Nurfiani, Dini (Nanyang Technological University, 2022)
Eruption forecasting and volcanic hazard assessments are not well constrained without insights on a volcano’s eruptive behavior and magma plumbing system. In this thesis I investigate the eruption behavior and magma plumbing system through a combination of petrological and seismic studies at Marapi volcano. First, I analyzed the compositions and textures of phenocrysts in recent volcanic bombs and applied mineral thermobarometry and conducted a joint inversion of receiver function and horizontal-to-vertical (H/V) spectral ratio of Rayleigh waves. Second, I investigated reversely-zoned orthopyroxene crystals via Fe-Mg interdiffusion to retrieve the time scales of the magmatic processes causing the reverse zoning. Third, I analyzed three recent eruptions for their spectral content, source location, seismic energy, and volcanic ash characteristics to gain insights on the fragmentation mechanism. The findings from this study can bring insights that are relevant for other similar arc volcanoes and their phreatic eruptions.